Islamic Scholars in Malay Archipelago: Sheikh Daud al-Fatani (1769-1847M) Contribution‘s in Fiqh al-Shafie - Mustapha, Ahmad Sharifuddin; Ali, Abdul Karim; Zainol, Nur Zainatul Nadra; Saparudin, Intan Farhana (Journal of Social Transformation and Regional Development, 2021)
Malay world had produced scholars who expert in fiqh, akidah, akhlak, Sufism, and another area. They actively disseminated Islam to local residents by producing plenty of publications as a valuable legacy to the Muslims, especially in the Malay archipelago. Among the scholars was Sheikh Daud bin Abdullah al-Fatani is known as a prolific scholar in various areas. However, his work in fiqh al-Shafie given less attention compared to other areas. This article examines the contribution of Sheikh Daud in writing descriptively and analyzes the works of fiqh al-Shafie. In order to achieve the objectives outlined, this article used the method of content analysis of these texts being entitled Bughyat al- Tullab, al-Saidu Wa al-Zabaih, al-Bahjat al-Saniyat, Mun al-Musalla, and Al-Hidayah Muta'allim. In addition, the method of semi-structured interviews was conducted to obtain additional data associated with the topic. The results showed Sheikh Daud gave a significant contribution to the development of Islam in the region of Malaya with the publication of scientific writing in the Fiqh Shafie area. He was able to do islah to the community around her by produced books and manuscripts. Those publications are still cited today.